2006
DOI: 10.1080/j157v06n02_07
|View full text |Cite
|
Sign up to set email alerts
|

Punica granatum(Pomegranate) Extract Is Active Against Dental Plaque

Abstract: In the present work, we studied the effect of the hydroalcoholic extract (HAE) from Punica granatum (pomegranate) fruits on dental plaque microorganisms. The study was conducted on 60 healthy patients (33 females and 27 males, with age ranging from 9 to 25 years) using fixed orthodontic appliances, and randomly distributed into 3 groups of 20 patients each. The first group (control) used distilled water, while the second and third groups used chlorhexidine (standard) and HAE as mouth-rinses, respectively. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(77 citation statements)
references
References 25 publications
2
68
0
Order By: Relevance
“…Pomegranate juice and fruit extracts normalized to punicalagins and a total pomegranate tannin fraction (TPT) from the fruit have been shown to inhibit the proliferation of human cancer cells and modulate inflammatory subcellular signaling pathways (Afaq et al, 2005;Seeram et al, 2005;Adams et al, 2006). The effects of pomegranate juice and extracts on molecular and cellular mechanisms has been researched on a systemic level where benefits for cardiovascular, prostate, dental, and metabolic health have been shown in the clinical literature (Aviram et al, 2000(Aviram et al, , 2002(Aviram et al, , 2004Esmaillzadeh et al, 2006;Menezes et al, 2006;Pantuck et al, 2006).…”
Section: Research Articlementioning
confidence: 99%
“…Pomegranate juice and fruit extracts normalized to punicalagins and a total pomegranate tannin fraction (TPT) from the fruit have been shown to inhibit the proliferation of human cancer cells and modulate inflammatory subcellular signaling pathways (Afaq et al, 2005;Seeram et al, 2005;Adams et al, 2006). The effects of pomegranate juice and extracts on molecular and cellular mechanisms has been researched on a systemic level where benefits for cardiovascular, prostate, dental, and metabolic health have been shown in the clinical literature (Aviram et al, 2000(Aviram et al, , 2002(Aviram et al, , 2004Esmaillzadeh et al, 2006;Menezes et al, 2006;Pantuck et al, 2006).…”
Section: Research Articlementioning
confidence: 99%
“…The only human trials examining the antibacterial properties of pomegranate extracts have focused on oral bacteria (Sastravaha et al, 2003;Menezes et al, 2006). However, several in vitro assays demonstrate its bacteriocidal activity against several highly pathogenic and sometimes antibiotic-resistant organisms.…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
“…These include anti-inflammatory, antitumoral, diabetes prevention/ treatment, antiulcer, antimicrobial, antiangiogenic, immunomodulating and antioxidant activities. The medicinal properties of this fruit have been widely investigated and numerous scientific papers have corroborated with its popular use (Prashanth et al, 2001;Braga et al, 2005;Menezes et al, 2006;Vasconcelos et al, 2006;Aquil, Ahmad, 2007;Oliveira et al, 2010;Johanningsmeier, Harris, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…These include anti-inflammatory, antitumoral, diabetes prevention/ treatment, antiulcer, antimicrobial, antiangiogenic, immunomodulating and antioxidant activities. The medicinal properties of this fruit have been widely investigated and numerous scientific papers have corroborated with its popular use (Prashanth et al, 2001;Braga et al, 2005;Menezes et al, 2006;Vasconcelos et al, 2006;Aquil, Ahmad, 2007;Oliveira et al, 2010;Johanningsmeier, Harris, 2011).Analyses of the antioxidant property of pomegranate have shown that this fruit is superior to other foods in terms of antioxidant effects, such as red wine, cranberries and green tea (Seeram et al, 2008). Moreover certain reports have shown considerable antioxidant activities of Punica granatum in several in vitro and in vivo experimental models (Chidambara et al, 2002;Cerda et al, 2003;Ricci et al, 2006;Bishayee et al, 2011).…”
mentioning
confidence: 96%